Direct detection of Mycobacterium tuberculosis rifampin resistance in bio-safe stained sputum smears - Lavania, Surabhi (PLoS One, 2017)
Direct smear microscopy of sputum forms the mainstay of TB diagnosis in resource-limited settings. Stained sputum smear slides can serve as a ready-made resource to transport sputum for molecular drug susceptibility testing. However, bio-safety is a major concern during transport of sputum/stained slides and for laboratory workers engaged in processing Mycobacterium tuberculosis infected sputum specimens. In this study, a bio-safe USP (Universal Sample Processing) concentration-based sputum processing method (Bio-safe method) was assessed on 87 M. tuberculosis culture positive sputum samples. Samples were processed for Ziehl-Neelsen (ZN) smear, liquid culture and DNA isolation. DNA isolated directly from sputum was subjected to an IS6110 PCR assay. Both sputum DNA and DNA extracted from bio-safe ZN concentrated smear slides were subjected to rpoB PCR and simultaneously assessed by DNA sequencing for determining rifampin (RIF) resistance. All sputum samples were rendered sterile by Bio-safe method. Bio-safe smears exhibited a 5% increment in positivity over direct smear with a 14% increment in smear grade status. All samples were positive for IS6110 and rpoB PCR. Thirty four percent samples were RIF resistant by rpoB PCR product sequencing. A 100% concordance (κ value = 1) was obtained between sequencing results derived from bio-safe smear slides and bio-safe sputum. This study demonstrates that Bio-safe method can address safety issues associated with sputum processing, provide an efficient alternative to sample transport in the form of bio-safe stained concentrated smear slides and can also provide information on drug (RIF) resistance by direct DNA sequencing.